Clinical Research Subject Recruitment: The Volunteer for Vanderbilt Research Program www.volunteer.mc.vanderbilt.edu - Harris, Paul A. (American Medical Informatics Association, 2005)
This article provides information concerning a novel research subject recruitment registry developed at Vanderbilt University. Project goals were (1) to provide a mechanism for lay individuals to self-enter information conveying interest in volunteering for clinical research and (2) provide tools for researchers to select and contact potential volunteers based on study-specific inclusion criteria. The registry was built and offered as an institutional resource to all university scientists conducting institutional review board–approved research. The authors present (1) a model for redesigning workflow associated with subject registration, volunteer retrieval, and subject contact; (2) details of a Web-based software application used as a focal point in designing workflow for our system; (3) descriptive statistics for volunteer and researcher use of the system during the first 32 months of operation; (4) cost estimates for the project; and (5) a set of recommendations for other medical centers wishing to adopt similar methodology.